The Potential of Facebook Utilization in Women’s Undergarments Luxury Fashion Brand - Aprilianty, Fitri; Nasution, Reza Ashari (School of Business and Management Institut Teknologi Bandung, 2017)
Abstract. The dynamic of global economy drives luxury fashion businesses to change. The primary channel of retailing for luxury fashion brand undergarment is offline stores because Luxury brands are expected to evoke uniqueness and exclusivity through high quality, premium pricing, and controlled distribution. With the exponential growth of various social media, however, luxury brands face challenges in how to maintain brand integrity while keep up with the social media trend. Facebook pages have emerged as a commonly used marketing communication tools and marketing channel, because visiting luxury fashion brand Facebook may stimulate consumers’ interest in using Facebook for shopping. The purpose of this paper is to examine how women’s undergarments luxury fashion brand using Facebook as a marketing tool and how consumers are interacting with the brand by measuring the number of fans, comments, and accuracy of information provided. This paper is based upon a content analysis, inquiring into 30 women’s undergarment luxury fashion brand Facebook pages. Data analysis revealed many undergarment luxury fashion brands appear to have in promoting their products and engaging customers through Facebook. One major problem was the absence of an updated Facebook page. The findings of this study can enable luxury brands to forecast the future purchasing behavior of their customers and provide a guide to managing their marketing activities as well. Keywords: Facebook, luxury fashion brand, women’s undergarment, content analysis